Safety and therapeutic effect of metronomic chemotherapy with cyclophosphamide and celecoxib in advanced breast cancer patients - Perroud, Herman A (2013)
Fil: Fil: Perroud, Herman A. Institute of Experimental Genetics. School of Medical Sciences. National University of Rosario; Rosario; Argentina